2015
DOI: 10.1038/ijos.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Role of saliva proteinase 3 in dental caries

Abstract: Salivary analysis can be used to assess the severity of caries. Of the known salivary proteins, a paucity of information exists concerning the role of proteinase 3 (PR3), a serine protease of the chymotrypsin family, in dental caries. Whole, unstimulated saliva was collected from children with varying degrees of active caries and tested using a Human Protease Array Kit and an enzyme-linked immunosorbent assay. A significantly decreased concentration of salivary PR3 was noted with increasing severity of dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…We have demonstrated, by immunocytochemistry, that salivary epithelial cells express cytoplasmic hCAP18/LL‐37 immunoreactivity; this probably reflects hCAP18 rather than LL‐37 as cleavage of hCAP18 to LL‐37 only occurs extracellularly . Human saliva contains proteinase 3, and thus an important enzyme that catalyzes the production of LL‐37 from hCAP18 is indeed present in the saliva . Interestingly, the central part of the cytoplasm showed only a weak hCAP18/LL‐37 signal, whereas the outer, peripheral region of the cytoplasm expressed strong hCAP18/LL‐37 immunoreactivity organized in a punctuate staining pattern.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We have demonstrated, by immunocytochemistry, that salivary epithelial cells express cytoplasmic hCAP18/LL‐37 immunoreactivity; this probably reflects hCAP18 rather than LL‐37 as cleavage of hCAP18 to LL‐37 only occurs extracellularly . Human saliva contains proteinase 3, and thus an important enzyme that catalyzes the production of LL‐37 from hCAP18 is indeed present in the saliva . Interestingly, the central part of the cytoplasm showed only a weak hCAP18/LL‐37 signal, whereas the outer, peripheral region of the cytoplasm expressed strong hCAP18/LL‐37 immunoreactivity organized in a punctuate staining pattern.…”
Section: Discussionmentioning
confidence: 82%
“…Human whole saliva has been shown to contain proteinase 3, suggesting that when hCAP18 is released from oral cells, it can be cleaved to LL‐37 extracellularly in the saliva . Whole saliva contains numerous desquamated epithelial cells and also neutrophils .…”
mentioning
confidence: 99%
“…However, the results reported by the authors are not unequivocal. Yang, Li et al (), Yang, Zhou et al () and Ranadheer et al () observed significantly increased sIgA concentration in patients belonging to high caries risk group with active caries compared to caries‐free patients. Similar results were obtained by Bagherian et al () and Al Amoudi et al ().…”
Section: Discussionmentioning
confidence: 94%
“…In the presented systematic literature review, the authors of the cited paper undertook the topic of salivary immunoglobulins, belonging to class IgA, IgG or IgM. These immunoglobulins play an important role in the immunological system mechanism as they are a part of humoural immunity and enable bacteria neutralization, which is significant in the process of caries development (Al Amoudi et al, ; Bagherian, Jafarzadeh, Rezaeian, Ahmadi, & Rezaity, ; de Farias et al, ; Doifode et al, ; Kuriakose, Sundaresan, Mathai, Khosla, & Gaffoor, ; Malcolm et al, ; Omar, Khattab, & Rashed, ; Pal, Mitra, Mishra, Saha, & Bhattacharya, ; Parisotto et al, ; Ranadheer, Nayak, Reddy, & Rao, ; Shifa, Muthu, Amarlal, & Rathna, ; Thaweboon, Thaweboon, Nakornchai, & Jitmaitree, ; Yang, Li et al, ; Yang, Zhou, et al, ; Colombo, Pereira, et al, ). However, the results reported by the authors are not unequivocal.…”
Section: Discussionmentioning
confidence: 99%
“…4 Salivary proteins have five roles: (a) for microbial agglutination, (b) for the lysis of microbial membranes, (c) for antifungal and (d) antivirus, and (e) is used as an immune regulatory processes immune regulation at mucosal tissues. 5 In addition, saliva has a very important role in neutralizing acidic conditions.…”
Section: Introductionmentioning
confidence: 99%